2000
DOI: 10.1016/s0960-9822(00)00443-7
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide interacts with the retinoblastoma pathway to control eye development in Drosophila

Abstract: Animal organ development requires that tissue patterning and differentiation is tightly coordinated with cell multiplication and cell cycle progression. Several variations of the cell cycle program are used by Drosophila cells at different stages during development [1] [2]. In imaginal discs of developing larvae, cell cycle progression is controlled by a modified version of the well-characterized mammalian retinoblastoma (Rb) pathway [3] [4], which integrates signals from multiple effectors ranging from growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 20 publications
4
36
0
Order By: Relevance
“…We show that the action of DNOS4 is reciprocal to RBF and additive or synergistic to dE2F, thus acting to relieve the negative effect of DNOS1 on cell proliferation during eye-disc development. Our results support the hypothesis that the DNOS family of proteins acts to modulate the entry of cells into the S phase of the cell cycle in the eye disc by interacting with the Rb pathway (Kuzin et al 2000; present study). RBF or E2F proteins themselves are potential direct targets for NO action, for example, via S-nitrosylation of cysteine residues by endogenous NO or NO donors (Stamler et al 2001); intriguingly, Rb is one of the several proteins identified in an in vivo screen for S-nitrosylated proteins in mammalian cells (Jaffrey et al 2001).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…We show that the action of DNOS4 is reciprocal to RBF and additive or synergistic to dE2F, thus acting to relieve the negative effect of DNOS1 on cell proliferation during eye-disc development. Our results support the hypothesis that the DNOS family of proteins acts to modulate the entry of cells into the S phase of the cell cycle in the eye disc by interacting with the Rb pathway (Kuzin et al 2000; present study). RBF or E2F proteins themselves are potential direct targets for NO action, for example, via S-nitrosylation of cysteine residues by endogenous NO or NO donors (Stamler et al 2001); intriguingly, Rb is one of the several proteins identified in an in vivo screen for S-nitrosylated proteins in mammalian cells (Jaffrey et al 2001).…”
Section: Discussionsupporting
confidence: 91%
“…NO acts as an antiproliferative factor during eye development; pharmacological inhibition of NOS activity results in an increase in the number of cells in the ommatidia (Kuzin et al 1996(Kuzin et al , 2000. We asked whether DNOS4 can act to suppress the antiproliferative action of NO and affect cell division in the developing eye.…”
Section: Ectopic Expression Of Dnos4 Increases the Cell Number In Thementioning
confidence: 99%
See 3 more Smart Citations